2013
DOI: 10.2174/1874331501307010011
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Carbon Dynamics of Crop Residue Mixtures in a Semiarid Long Term No-Till System: Effects on Soil Organic Carbon

Abstract: Plant residues decomposition transfers organic matter and nutrients to soil, and plays a decisive role in carbon (C) cycling. The aims of our study were to analyze under realistic field conditions the annual decomposition and C dynamics of crop residues mixtures under long-term no-till management and their effect on soil organic carbon (SOC). Three treatments were evaluated: soybean monoculture, soybean rotation (maize as preceding crop), and maize rotation (soybean as preceding crop). In each treatment soil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Anyway, C input was not enough to maintain a SOC content of 33.3 g C kg -1 (Table 1) and hence, according to and Domínguez et al (2009), a decrease in SOC and POC throughout the experiment could have been expected regardless of TS and NF. Despite the higher C input due to N fertilization, it has been reported that continuous addition of N at high rates could lead to accelerated rates of residue decomposition and of organic soil C mineralization (Khan et al 2007;Poirier et al 2009;Casado-Murillo and Abril 2013;Melchiori et al 2014). Conversely, higher C input does not always lead to an increased SOC content since this depends on the balance between increased input and higher C dioxide emission.…”
Section: Bulk Soil and Particulate Organic Carbon And Anaerobic Nitrogen Changesmentioning
confidence: 99%
“…Anyway, C input was not enough to maintain a SOC content of 33.3 g C kg -1 (Table 1) and hence, according to and Domínguez et al (2009), a decrease in SOC and POC throughout the experiment could have been expected regardless of TS and NF. Despite the higher C input due to N fertilization, it has been reported that continuous addition of N at high rates could lead to accelerated rates of residue decomposition and of organic soil C mineralization (Khan et al 2007;Poirier et al 2009;Casado-Murillo and Abril 2013;Melchiori et al 2014). Conversely, higher C input does not always lead to an increased SOC content since this depends on the balance between increased input and higher C dioxide emission.…”
Section: Bulk Soil and Particulate Organic Carbon And Anaerobic Nitrogen Changesmentioning
confidence: 99%
“…Decomposition of plant residues is essential for the cycling of elements and the provisioning of nutrients to plants (Casado‐Murillo & Abril, 2013), and therefore for the sustainable management of agricultural systems (Hättenschwiler et al., 2005; Lavelle et al., 1993; Prescott, 2005). Litter breakdown depends on physical and chemical characteristics of the environment, litter nutrient concentrations and structure and the decomposer community (Couteaux et al., 1995; Knacker et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The application of organic material (e.g., crop residues) is one of the major sustainable management practices of cropland soils, and it increases or reduces the amounts of carbon inputs or outputs; improves soil physical, chemical and biological properties; potentially accomplishes the restoration of SOC and improves soil fertility [ 4 – 7 ]. It is also important for carbon transformation for conventional agriculture cropping systems in northeast China by transferring organic matter and nutrients to the soil [ 8 – 11 ]. Most studies in this area reveal that all of the tested organic materials show a gradual decreasing trend over time even though there are decomposition differences among these organic materials [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%